The Palgrave Handbook of Feminism and Sport, Leisure and Physical Education (Palgrave Macmillan UK, 2018)
This handbook provides an original, comprehensive and unparalleled overview of feminist scholarship in sport, leisure and physical education. It captures the complexities of past, current and future developments in feminism while highlighting its theoretical, methodological and empirical applications. It also critically engages with policy and practice issues for women and girls taking part in sport and leisure pursuits and in physical education provision. The Palgrave Handbook of Feminism and Sport, Leisure and Physical Education is international in scope and includes the work of established and emerging feminist scholars. It will be of interest to students and scholars across a range of disciplines, including sociology, gender studies, sport sciences, and sports business and management.